The Benefits and Problems in the Implementation of the Special Effort of Rice, Corn, Soybean Production Enhancement Program - Darwis, Valeriana; Muslim, Chairul; Hangga Saputra, Yonas (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The Special Efforts of Rice, Corn and Soybean Production Enhancement Program has been performed since 2015 and in its implementation several benefits and problems have been identified. The aim of this research was to identify the benefits, problems as well as the adoption and feedback of the application of technological innovation in East Java Province. The survey was conducted in June 2019 with data and information analysis conducted descriptively with the discussion utilized the deepening results through focus group discussion. The deepening results showed the benefits of participating in the program, which were: increased institutional activity, increased knowledge, and increased productivity. On the other hand, the problems were: the recipient was not in accordance with CPCL/prospective farmers and location; seed aid was not enough, it was not as expected and it was too late; Agricultural machine tools aid was still less and the size did not match the cultivated land. The expected feedbacks from technological innovation side were: (i) seed varieties aid adjusted to the location and farmers expectation also the arrival has to be on time and right amount; (ii) agricultural machine tools aid was not only for rice, the type and size of the agricultural machine tools followed the conditions of farmers' land and training for the operators who operate it.